THEORETICAL APPROACHES TO DEFINING THE ESSENCE AND FUNCTIONS OF PUBLIC FINANCE - Goncharenko, M. (Pressing Problems of Public Administration, 2020)
The article is devoted to the study of scientific ideas about the financial security of the public interest and the systematization of basic theoretical approaches to determining the nature and functions of public finance.The historical aspect of the development of understanding the content of public finances is analyzed, based on the need to ensure the functions of the state and satisfy the public interest. The most accurate interpretation of the category “public interest” - common interests, which can be considered as a generalization of personal, group interests, without satisfaction and realization of which it is impossible, on the one hand, to realize private interests, on the other - to ensure integrity, stability and normal development, states, nations, social strata and societies in general.It is substantiated that, in the modern sense, public finances are public relations that arise not only in the process of managing only the state or other “public unions”, but arise primarily in the process of satisfying the public interest.The differences between public and private finances are considered, as well as some approaches to the structuring of public finances and the relationship between the concepts of “public” and “state” finances.The statement that public finances are a sphere of the financial system, and include public finances, local finances, finances of state corporations and social insurance funds, have the characteristics of imperative, transparency and publicity (belonging to a public union, society).It is proved that public finance management is the main activity of any state in any period of its historical development. Based on the allocation of distribution, control and social functions, the important role of public finances in the socio-economic development of society is proved.In determining the directions of further research, it is noted that in scientific developments there are many controversial issues regarding the structuring of public finances, determining the content of their components and the relationships between them.